2021
DOI: 10.3171/2021.6.peds21143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hypertonic saline on intracranial pressure and cerebral autoregulation in pediatric traumatic brain injury

Abstract: OBJECTIVE Hypertonic saline (HTS) is commonly used in children to lower intracranial pressure (ICP) after severe traumatic brain injury (sTBI). While ICP and cerebral perfusion pressure (CPP) correlate moderately to TBI outcome, indices of cerebrovascular autoregulation enhance the correlation of neuromonitoring data to neurological outcome. In this study, the authors sought to investigate the effect of HTS administration on ICP, CPP, and autoregulation in pediatric patients with sTBI. METHODS Twenty-eight p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Lung-protective ventilation, 36 early orthostatic exercises, 37 and propofol/vasopressor use 38,39 have no detrimental effect on CA. Short-term hyperventilation (PaCO 2 : 37 mm Hg→ 28 mm Hg) may improve dynamic CA, 40 hypertonic (20%) saline may or may not improve CA status, 41,42 and decompressive craniectomy may either have no effect or revert impaired CA to an intact CA pattern, primarily due to its ICP-lowering effect. 43 Unanswered Questions/Future Research Future studies may examine the effect of CA status and provocative testing on brain-tissue oxygenation and whether an intervention bundle may allow clinicians to preserve and/or reverse CA status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung-protective ventilation, 36 early orthostatic exercises, 37 and propofol/vasopressor use 38,39 have no detrimental effect on CA. Short-term hyperventilation (PaCO 2 : 37 mm Hg→ 28 mm Hg) may improve dynamic CA, 40 hypertonic (20%) saline may or may not improve CA status, 41,42 and decompressive craniectomy may either have no effect or revert impaired CA to an intact CA pattern, primarily due to its ICP-lowering effect. 43 Unanswered Questions/Future Research Future studies may examine the effect of CA status and provocative testing on brain-tissue oxygenation and whether an intervention bundle may allow clinicians to preserve and/or reverse CA status.…”
Section: Discussionmentioning
confidence: 99%
“…Lung-protective ventilation, 36 early orthostatic exercises, 37 and propofol/vasopressor use 38,39 have no detrimental effect on CA. Short-term hyperventilation (PaCO 2 : 37 mm Hg→ 28 mm Hg) may improve dynamic CA, 40 hypertonic (20%) saline may or may not improve CA status, 41,42 and decompressive craniectomy may either have no effect or revert impaired CA to an intact CA pattern, primarily due to its ICP-lowering effect 43 …”
Section: Key Questions and Answers Based On Review Of The Published L...mentioning
confidence: 99%
“…A recent comparative effectiveness study of pediatric TBI patients demonstrated bolus dosing of hypertonic saline to be superior to mannitol in reduction of intracranial hypertension[ 68 ]. Some evidence suggests that hyperosmolar therapy is more likely to be effective in reducing intracranial hypertension when there is evidence of efficient cerebrovascular pressure reactivity (CVPR)[ 69 - 71 ]. Emerging research has demonstrated several biomarkers that target the blood-brain barrier or receptors of aquaporin-4 or vasopressin V1a to mitigate cerebral edema, although these are not yet standard treatment targets in clinical care[ 72 ].…”
Section: Targets For Neuroprotection In the Picumentioning
confidence: 99%